Characterizing Photon Beam Properties of a TrueBeam STx Linear Accelerator: An Evaluation of Geant4/GATE Monte Carlo Simulation Tool Performance - Lam, P. H.; Dung, P. T.; Trung, P. Q. (National Research and Innovation Agency, 2024)
Purpose: This study aims to investigate the characteristics of photon beams from TrueBeam STx, comparing flattening filter (FF) and flattening filter free (FFF) configurations between measurements and Monte Carlo simulation. Instruments and methods: The Geant4/GATE simulation toolkit was utilized to simulate percentage depth dose (PDD), off-axis distance profiles (profiles), dmax, TPR20/10, surface dose, field size, penumbra, flatness, and symmetry. Subsequently, these simulated results were compared with experimental measurements and evaluated using the gamma index method. Results: There was a good agreement between simulation and experimental measurement results in modeling the PDD and profile of photon beams. All gamma passing rate indices exceeded 97 %, 94 %, and 90 % with criteria of 3 % and 3 mm, 2 % and 2 mm, and 1 % and 1 mm, respectively. The calculated results of beam characteristics (dmax, TPR20/10, surface dose, field size, penumbra, flatness, and symmetry) were highly compatible with experimental measurements, with discrepancies less than 3 %, except for the surface dose of the 6MV FF photon beam, which had an error of 3.83 %. Conclusion: The Geant4/GATE simulation toolkit provided accurate results for simulating and investigating photon beam characteristics, aligning closely with experimental measurements.